Calibration of Dial Indicator Using Calibration Tester with JIS B 7503 Standard - Dodi Sofyan Arief; Amri Pahlevi; Agus Surya Permana (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2021)
The measurement process is the most important part of the production process in the industrial world. Obtaining good measurement results can not be separated from using measuring instruments that are always maintained. Subsequence, the maintenance of calibration procedures must be carried out periodically based on a predetermined time limit. The calibration process is an activity to compare standard quantities between measuring instruments and testers that are in accordance with the measuring instrument and carried out periodically. The implementation of the calibration process often has generates an uneven value where this value is better known as the uncertainty value. This research objective is to determine the uncertainty value of the measuring instrument of a dial indicator using the JIS B 7503 Standard. The calibration can control the quality of the equipment used, and can show whether the tool is feasible or not to be used.